A CORRECTION - Souter, A. (The journal of theological studies, 1913)
In the last number of the JOURNAL (p. 339), in making the statement that ‘the musical notation’ in the Egerton MS 874 (saec. ix) of the British Museum ‘is among the earliest known’, I had hastily assumed that this notation was contemporary with the rest of the MS, with which I was particularly concerned. Mr H. M. Bannister has consulted the British Museum authorities, and they are agreed that ff. 68v–69v, the portion containing the musical notation, are an insertion by a hand of saec. xi/xii at earliest. My statement therefore falls to the ground.